Crafting and reinforcing the state through security privatisation: territorialisation as a public–private state project in East Jerusalem - Volinz, Lior (Policing and society, 2019)
A growing number of police and security functions, previously considered within the exclusive domain of the state, are being outsourced to private security actors. This article argues that the privatisation of security provision can reinforce, rather than erode, the state, by contributing to state actors’ capacity to pursue the territorialisation of areas beyond the full grasp of the state. Exploring the outsourced security provision at Jewish-Israeli settlement compounds in East Jerusalem, I attend to a Public-Private security assemblage which performs Israeli sovereignty in an occupied territory. I suggest that by outsourcing security provision, in Israel/Palestine and elsewhere, state actors are able to differentially distribute (in)security while evading accountability and deflecting public and legal challenges to controversial state-led projects. In examining the relations formed between state and non-state security actors within an emerging local and urban assemblage, I argue that state authority and responsibility can be diffused into multiple nodes of private authority in the operation, performance and supervision of security and violence - while at the same time keeping the state monopoly over legitimate violence intact.